2018
DOI: 10.1021/acs.langmuir.8b01979
|View full text |Cite
|
Sign up to set email alerts
|

Opto-Thermophoretic Attraction, Trapping, and Dynamic Manipulation of Lipid Vesicles

Abstract: Lipid vesicles are important biological assemblies which are critical to biological transport processes, and vesicles prepared in the lab are a workhorse for studies of drug delivery, protein unfolding, biomolecular interactions, compartmentalized chemistry, and stimuli-responsive sensing. Optical tweezers, the current method for holding lipid vesicles in place for single-vesicle studies, suffers from limitations such as high optical power, rigorous optics, and a small difference in the refractive indices of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 56 publications
0
44
1
1
Order By: Relevance
“…As a heat delivery mechanism recent progress in the field of thermoplasmonics 12,13 has shown that nanoscale structures can efficiently transduce light into heat, thereby enabling a high degree of control over the amount and extent of heat deposited to a specific area 14 . More recently, efforts have focused on exploiting these thermal gradients to manipulate or characterize particles within the fluid 15,16 . Thermal gradients, broadly speaking, alter the dynamics of the particles at two distinct levels: at the particle and fluid level, respectively.…”
mentioning
confidence: 99%
“…As a heat delivery mechanism recent progress in the field of thermoplasmonics 12,13 has shown that nanoscale structures can efficiently transduce light into heat, thereby enabling a high degree of control over the amount and extent of heat deposited to a specific area 14 . More recently, efforts have focused on exploiting these thermal gradients to manipulate or characterize particles within the fluid 15,16 . Thermal gradients, broadly speaking, alter the dynamics of the particles at two distinct levels: at the particle and fluid level, respectively.…”
mentioning
confidence: 99%
“…In the presence of a surfactant solution, heating effects generate a thermoelectric field, which induces an attractive thermophoretic force that draws particles towards the hot area. Zheng's group recently made notable contributions to this field [175][176][177][178][179][180][181][182][183][184][185] by developing light-directed thermoelectric field-assisted extremely low-power opto-thermoelectric tweezers. Ndukaife et al developed the first-ever optothermo-electrohydrodynamic tweezers very recently, which can trap and manipulate objects on an even smaller scale 186 .…”
Section: Thermal Controlmentioning
confidence: 99%
“…Optical tweezer techniques have been widely used in studies of vesicles, including force analysis 266 and component analysis within vesicles 267 , extracellular interactions between vesicles and their ligands and other cells 268 , dragging and selection of individuals for further control 269 and connection of isolated vesicles for sculpting and fusing biomimetic networks 270 . In 2018, Zheng et al demonstrated the use of plasmonic heating to trap vesicles in a temperature gradient, allowing long-range attraction, parallel trapping and dynamic manipulation 183 . In the same year, Oh et al reported an integrated nanogap plasmonic sensing platform to trap sub-100 nm vesicles for real-time Raman spectroscopy imaging (Fig.…”
Section: Applications Of Plasmonic Tweezersmentioning
confidence: 99%
“…The above studies show that the thermal drive has great potential for contactless separation and enrichment of nanoparticles, and the thermal behavior of droplets at different temperatures is of great significance in biosensors. However, the thermal drive may cause thermophysical changes in biological products such as lipid vesicles (Hill et al., 2018).…”
Section: Simulation Of Driving Modesmentioning
confidence: 99%